Method for recovering metal from waste ternary lithium battery positive electrode material

By using lithium-ion selective permeation membranes and electrode sheet technology in the lithium battery recycling process, the directional migration of lithium and the enrichment of transition metals have been achieved, solving the problems of low lithium purity and incomplete separation, providing an efficient path for the recovery of valuable metals, and promoting the sustainable development of the new energy industry.

CN121204673APending Publication Date: 2025-12-26JINGMEN GEM NEW MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511361402.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-23
Publication Date
2025-12-26

AI Technical Summary

Technical Problem

In existing technologies, lithium battery recycling processes suffer from low lithium purity, incomplete separation of transition metals, and complex processes, leading to resource waste and environmental pollution.

Method used

A lithium-ion selective permeation membrane is used to separate the electrolytic cell. The electrode sheet is used as the anode to carry out the redox reaction, realizing the directional migration and enrichment of lithium. Transition metals are enriched in the anode chamber through a precise separation mechanism. Combined with a step-by-step control strategy for post-processing, high-purity recovery is achieved.

Benefits of technology

It improves the recovery rate and purity of lithium, deeply separates transition metals, simplifies the process, realizes efficient and environmentally friendly recycling of valuable metals, and promotes the sustainable development of the new energy industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005609145840000131
    Figure BDA0005609145840000131
  • Figure BDA0005609145840000141
    Figure BDA0005609145840000141
Patent Text Reader

Abstract

The invention provides a method for recycling metal from a waste ternary lithium battery positive electrode material. The method comprises the following steps: mixing the waste ternary lithium battery positive electrode material, a binder, a conductive agent and an organic solvent to prepare mixed slurry; coating a current collector with the mixed slurry to obtain an electrode plate; taking the electrode plate as an anode, taking an inert electrode as a cathode, dividing the electrolytic tank into an anode chamber and a cathode chamber by adopting a lithium ion selective permeable membrane, and carrying out oxidation-reduction reaction, so that transition metal ions are dissolved out from electrolyte of the anode chamber, and lithium phosphate precipitates are formed in the cathode chamber; and carrying out post-treatment on the electrolyte in the anode chamber to obtain the nickel-cobalt mixed metal salt. According to the method, the problems of low lithium purity, incomplete transition metal separation, complex process and the like in the traditional recovery technology are solved, and an efficient, environment-friendly and controllable process path is provided for high-valued recovery of valuable metals of the waste ternary lithium batteries.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the field of lithium ion battery recycling, and particularly relates to a method for recovering metals from waste ternary lithium battery positive electrode materials. BACKGROUND

[0002] With the rapid development of new energy vehicles, portable electronic devices and other fields, ternary lithium batteries have become one of the current mainstream energy storage devices due to their high energy density and long cycle life. The positive electrode material of ternary lithium battery is mainly composed of transition metals such as nickel (Ni), cobalt (Co), manganese (Mn) and lithium (Li). Cobalt and nickel are scarce strategic resources, and lithium, as the core raw material of the new energy industry, has limited global reserves and uneven distribution.

[0003] However, the service life of lithium ion batteries is generally 5-8 years, and a large number of lithium ion batteries will enter the scrap stage every year. If the waste lithium batteries are not properly recycled, not only will it cause serious waste of valuable metal resources such as nickel, cobalt and lithium, but also will cause persistent pollution to the soil, water and ecological environment due to the leakage of heavy metals (such as cobalt and nickel) and electrolyte (containing fluoride and organic solvents) in the battery, threatening human health. Therefore, efficient recovery of metals such as nickel, cobalt and lithium from waste ternary lithium battery positive electrode materials and realization of resource recycling are the inevitable requirements for alleviating resource shortage, reducing environmental pollution and supporting the sustainable development of the new energy industry.

[0004] Currently, the metal recovery technology of waste ternary lithium battery positive electrode materials mainly includes direct regeneration method, pyrometallurgy and hydrometallurgy. The direct regeneration method is simple, but cannot fundamentally restore the material structure; the pyrometallurgical method has large processing capacity, but consumes a large amount of electricity and causes loss of precious metals and emission of a large amount of harmful gases; the hydrometallurgical method is widely used, but consumes a large amount of chemicals, and has the problems of complex process, low purity of lithium metal recovery and incomplete separation of transition metals.

[0005] Therefore, it is an urgent technical problem to develop an efficient process that can simultaneously realize high-purity recovery of lithium metal and deep separation of transition metals. SUMMARY

[0006] In view of the deficiencies of the prior art, the purpose of the present application is to provide a method for recovering metals from waste ternary lithium battery positive electrode materials. In the method provided by the present application, the precise screening effect of the lithium ion selective permeation membrane is used to realize the directional migration and enrichment of lithium in the electrolysis stage, thereby avoiding the pollution of transition metal ions to the lithium phase from the source, and the lithium recovery rate and recovery purity are synergistically improved. At the same time, the enrichment of transition metals in the electrolyte of the anode chamber is realized, and then the deep separation of lithium ions and transition metal ions is realized, and the high-purity directional recovery is completed. Therefore, by means of the precise separation mechanism and the step-by-step control strategy, the problems of low lithium purity, incomplete separation of transition metals and complex process in the traditional recovery technology are simultaneously solved, and an efficient, environmentally friendly and controllable process path is provided for the high-value recovery of valuable metals from waste ternary lithium batteries, which has important significance for promoting the resource circulation and sustainable development of the new energy industry.

[0007] To achieve this purpose, the present application adopts the following technical solutions:

[0008] In a first aspect, the present application provides a method for recovering metals from waste ternary lithium battery positive electrode materials, which comprises the following steps:

[0009] Mixing the waste ternary lithium battery positive electrode material, the binder, the conductive agent and the organic solvent to obtain a mixed slurry; coating the mixed slurry on the current collector to obtain an electrode sheet.

[0010] Using the electrode sheet as the anode and the inert electrode as the cathode, the electrolytic cell is divided into an anode chamber and a cathode chamber by a lithium ion selective permeation membrane, and an oxidation-reduction reaction is carried out, so that transition metal ions are dissolved out in the electrolyte of the anode chamber, and lithium phosphate precipitates are formed in the cathode chamber.

[0011] The electrolyte of the anode chamber is subjected to post-treatment to obtain a nickel-cobalt mixed metal salt.

[0012] In the method provided by the present application, the waste ternary lithium battery positive electrode material is converted into an anode with electrochemical activity, which provides an efficient reaction interface for the deep separation of transition metals and the directional migration of lithium ions in the subsequent electrolysis process. Compared with directly putting the positive electrode material powder into the electrolyte, the electrode sheet form can make the waste material fully contact with the electrolyte, reduce the mass transfer resistance, and increase the dissolution rate of transition metals to more than 95%. At the same time, the reaction rate per unit area can be precisely controlled to avoid the dissolution of impurities caused by local over-reaction. In addition, using the electrode sheet as the anode can avoid the filtration problem caused by the suspension of the powder-shaped material in the electrolyte. The stable structure formed by the binder can prevent the rapid dissolution of fluorides in the waste material and reduce the corrosion of the electrolyte and the membrane material.

[0013] In the method provided by the application, the precise screening effect of the lithium ion selective permeation membrane is used to realize the directional migration and enrichment of lithium in the electrolysis stage, to avoid the pollution of transition metal ions to the lithium phase from the source, to synergistically improve the lithium recovery rate and recovery purity, and to realize the enrichment of transition metals in the electrolyte in the anode chamber, to realize the deep separation of lithium ions and transition metal ions, and to complete the directional recovery of high-purity. Therefore, the application synchronously solves the problems of low lithium purity, incomplete separation of transition metals and complex process in the traditional recovery technology by using the precise separation mechanism and the step-by-step control strategy, and provides an efficient, environmentally friendly and controllable process path for the high-value recovery of valuable metals from waste ternary lithium batteries, which has important significance for promoting the resource circulation and sustainable development of the new energy industry.

[0014] It should be noted that the source of the waste ternary lithium battery positive material is not limited by the application. For example, it can be a positive material disassembled from a waste ternary lithium battery or a waste material generated in the production process of the positive material.

[0015] Preferably, before the waste ternary lithium battery positive material, the binder, the conductive agent and the organic solvent are mixed, the waste ternary lithium battery positive material is activated to reduce the transition metal in the waste ternary lithium battery positive material.

[0016] The purpose of the activation treatment of the waste ternary lithium battery positive material in the application is to reduce the transition metal in the waste ternary lithium battery positive material, so that the transition metal is more easily dissolved into low-valence ions (such as Ni 2+ , Co 2+ ) in the subsequent electrolysis process, and the electrolysis efficiency is improved.

[0017] Preferably, in the process of the activation treatment, the reducing agent used includes any one or a combination of at least two of citric acid, ascorbic acid or oxalic acid.

[0018] Preferably, the temperature of the activation treatment is 150-300℃, for example, it can be 150℃, 200℃, 250℃ or 300℃, etc.

[0019] Preferably, the binder includes any one or a combination of at least two of polyvinylidene fluoride, butadiene rubber or carboxymethyl cellulose.

[0020] Preferably, the conductive agent includes any one or a combination of at least two of conductive carbon black, carbon nanotube or graphene.

[0021] The type of the organic solvent is not limited by the application. For example, it can be N,N-dimethylacetamide, etc.

[0022] Preferably, the solid content of the mixed slurry is 30-70 wt%, for example, it can be 30 wt%, 40 wt%, 50 wt%, 60 wt%, or 70 wt%.

[0023] Preferably, the current collector comprises a graphite sheet.

[0024] Preferably, the inert electrode includes any one of a graphite electrode, a titanium electrode, or a platinum electrode.

[0025] Preferably, the lithium-ion selective permeation membrane is any one of a lithium-type molecular sieve, a ceramic-polymer composite membrane, a ceramic membrane, or a modified perfluorosulfonic acid resin membrane. For example, the lithium-type molecular sieve can be an LTA-type or Y-type molecular sieve, which achieves selectivity for Li+ ions through a micropore size sieving effect (pore size matching the Li+ diameter). + Its permeability is much higher than that of Ni. 2+ Co 2+ It is resistant to acid and alkali corrosion; the ceramic-polymer composite membrane can be a LATP (lithium aluminum titanium phosphate) and PVDF (polyvinylidene fluoride) composite membrane, which combines the high selectivity of inorganic ceramics with the flexibility of polymers, ensuring both the permeation flux of Li+ and improving the mechanical strength of the membrane; the ceramic membrane can be a lithium aluminum titanium phosphate membrane or a lithium lanthanum zirconium oxide membrane, etc.; the modified perfluorosulfonic acid resin membrane can be a lithium-type modified Nafion membrane, which achieves preferential Li+ transport by introducing lithium ion exchange groups (-SO3Li) and utilizing ion exchange and hydrophilic channels, and has good flexibility and strong processability.

[0026] Preferably, the electrolyte in the anode chamber and the electrolyte in the cathode chamber are both ammonium phosphate solutions.

[0027] This invention uses ammonium phosphate solution as the electrolyte, which can utilize the PO4 generated by its dissociation. 3- It reacts autonomously with Li+ that migrates to the cathode chamber to form lithium phosphate precipitate, eliminating the need for additional lithium precipitation agents and simplifying the process. At the same time, its weak buffer system (pH 6.5-8.0) can reduce metal ion precipitation in the anode chamber. Combined with a lithium-ion selective membrane, it can achieve efficient separation of Li+ from Ni and Co ions, improving the recovery rate of lithium, nickel, and cobalt and the purity of the product. Furthermore, ammonium phosphate is easy to recycle, reducing costs and environmental pollution risks.

[0028] Preferably, the pH of the electrolyte in the anode chamber and the electrolyte in the cathode chamber is 6.5-8, for example, it can be 6.5, 7, 7.5 or 8.

[0029] Preferably, the parameters of the redox reaction include:

[0030] The electrolysis voltage is 2-4V, for example, 2V, 3V or 4V, etc., the reaction temperature is 25-60℃, for example, 25℃, 30℃, 40℃, 50℃ or 60℃, etc., the current density is 10-200mA / cm 2 , for example, 10mA / cm 2 , 50mA / cm 2 , 100mA / cm 2 , 150mA / cm 2 or 200mA / cm 2 , etc.

[0031] Preferably, the post-treatment comprises the following steps:

[0032] The electrolyte in the anode chamber is subjected to acidification treatment, and then an oxidizing agent is added, so that Mn 2+ is oxidized to manganese oxide precipitate; filtration is then performed, and the filtrate is subjected to co-extraction of nickel and cobalt ions to obtain a mixed salt of nickel salt and cobalt salt.

[0033] The present application takes advantage of the characteristics of Mn 2+ being easily oxidized to high-valence insoluble substance (MnO2), and realizes deep removal of manganese without affecting Ni 2+ , Co 2+ , with simple process operation, high separation efficiency and suitability for industrial application.

[0034] It should be noted that the oxidizing agent needs to be in excess to ensure complete oxidation of Mn 2+ , and the pH of the system during oxidation is ≤5.0 to avoid oxidation of Ni 2+ , Co 2+ .

[0035] Preferably, the acid solution added during the acidification treatment comprises sulfuric acid.

[0036] Preferably, the pH of the electrolyte after the acidification treatment is 2-5, for example, 2, 3, 4 or 5, etc.

[0037] The present application limits the pH of the electrolyte after acidification treatment to 2-5, which ensures that Mn 2+ exists in a free state, promotes efficient oxidation, and at the same time inhibits the hydrolysis and precipitation of Ni 2+ , Co 2+ , ensuring that the two are stably present in the solution and avoiding co-precipitation; in addition, it creates a suitable environment for the subsequent precipitation reaction with sulfide solution, improving the precipitation efficiency.

[0038] Preferably, the temperature of the acidification treatment is 50-70℃, for example, 50℃, 60℃ or 70℃, etc.

[0039] Preferably, the extractant used in the process of the co-extraction comprises DY319 and / or HBL110.

[0040] Preferably, in the process of the co-extraction, the temperature is 30-80℃, for example, it can be 30℃, 50℃ or 80℃, etc.

[0041] Preferably, the method comprises the following steps:

[0042] (1) The waste and old ternary lithium battery positive electrode material is ground and sieved, and then dried at 100-110℃ (for example, it can be 100℃, 105℃ or 110℃, etc.) for 1-3h (for example, it can be 1h, 2h or 3h, etc.), to obtain a waste and old ternary lithium battery positive electrode material powder with a particle size D50 < 100 mesh (for example, it can be 80 mesh, 60 mesh, 50 mesh or 30 mesh, etc.).

[0043] The waste and old ternary lithium battery positive electrode material powder and a reducing agent are mixed to perform an activation treatment to reduce transition metals in the waste and old ternary lithium battery positive electrode material powder; wherein the reducing agent comprises any one or a combination of at least two of citric acid, ascorbic acid or oxalic acid; the temperature of the activation treatment is 150-300℃.

[0044] (2) The waste and old ternary lithium battery positive electrode material powder after the activation treatment, a binder, a conductive agent and an organic solvent are mixed to prepare a mixed slurry with a solid content of 30-70wt%; wherein the binder comprises any one or a combination of at least two of polyvinylidene fluoride, styrene-butadiene rubber or carboxymethyl cellulose, and the conductive agent comprises any one or a combination of at least two of conductive carbon black, carbon nanotube or graphene.

[0045] The mixed slurry is coated on a graphite sheet and dried to obtain an electrode sheet.

[0046] (3) The electrode sheet is used as an anode, an inert electrode is used as a cathode, a lithium ion selective permeation membrane is used to separate an electrolytic cell into an anode chamber and a cathode chamber, and an oxidation-reduction reaction is performed to dissolve nickel ions, cobalt ions and manganese ions in the electrolyte in the anode chamber and form lithium phosphate precipitates in the cathode chamber.

[0047] Wherein, the lithium ion selective permeation membrane is any one of a lithium type molecular sieve, a ceramic-polymer composite membrane, a ceramic membrane or a modified perfluorosulfonic acid resin membrane, the inert electrode comprises any one of a graphite electrode, a titanium electrode or a platinum electrode, the electrolyte in the anode chamber and the electrolyte in the cathode chamber are both ammonium phosphate solutions with a pH of 6.5-8; the parameters of the oxidation-reduction reaction include: an electrolytic voltage of 2-4V, a reaction temperature of 25-60℃, and a current density of 10-200mA / cm 2 .

[0048] (4) The electrolyte of the cathode chamber is filtered and then purified to obtain a battery-grade lithium phosphate product.

[0049] The electrolyte of the anode chamber is post-treated to obtain a nickel-cobalt-manganese mixed metal powder, and the specific steps include:

[0050] (a) Adding an acid solution to the electrolyte in the anode chamber and performing acidification treatment at a temperature of 50-70 DEG C to adjust the pH value of the electrolyte to 2-5, and then adding an oxidizing agent and reacting at a temperature of 20-60 DEG C to make Mn 2+ oxidized to manganese oxide precipitate, and then filtered to obtain a manganese-removed filtrate; wherein the oxidizing agent includes hydrogen peroxide.

[0051] (b) Co-extracting nickel and cobalt ions from the manganese-removed filtrate, and then stripping to transfer the nickel and cobalt ions to the aqueous phase, and after concentration and crystallization, a mixed salt of nickel salt and cobalt salt is obtained; wherein the extractant used in the co-extraction process includes DY319 and / or HBL110, and the temperature in the co-extraction process is 30-80 DEG C.

[0052] The numerical range of the present application includes not only the above-mentioned point values, but also any point values between the above-mentioned numerical ranges which are not mentioned, and due to the limited space and for the sake of simplicity, the present application does not enumerate the specific point values included in the range.

[0053] Compared with the prior art, the present application has the following beneficial effects:

[0054] (1) In the method provided by the present application, the waste ternary lithium battery positive electrode material is converted into an anode with electrochemical activity, which provides an efficient reaction interface for the deep separation of transition metals and the directional migration of lithium ions in the subsequent electrolysis process. Compared with directly putting the positive electrode material powder into the electrolyte, the electrode sheet form can make the waste material fully contact with the electrolyte, reduce the mass transfer resistance, and increase the dissolution rate of transition metals to more than 95%. At the same time, the reaction rate per unit area can be accurately controlled to avoid local over-reaction caused by impurity dissolution. In addition, using the electrode sheet as the anode can avoid the filtration problem caused by the suspension of the powder-shaped material in the electrolyte, and the stable structure formed by the binder can prevent the rapid dissolution of fluorides in the waste material and reduce the corrosion of the electrolyte and the membrane material.

[0055] (2) The method provided by the application realizes directional migration and enrichment of lithium in the electrolysis stage by means of the precise screening effect of the lithium ion selective permeation membrane, avoids pollution of transition metal ions to the lithium phase from the source, and cooperatively improves the lithium recovery rate and the recovery purity; meanwhile, the transition metals are enriched in the electrolyte in the anode chamber, the lithium ions and the transition metal ions are deeply separated, and high-purity directional recovery is completed. Therefore, the application synchronously solves the problems of low lithium purity, incomplete separation of transition metals and complex process in the traditional recovery technology by means of the precise separation mechanism and the step-by-step control strategy, and provides an efficient, environmentally friendly and controllable process path for high-value recovery of valuable metals from waste ternary lithium batteries, which has important significance for promoting resource recycling and sustainable development of the new energy industry. DETAILED DESCRIPTION

[0056] The technical solutions of the application will be further described by specific embodiments. Those skilled in the art should understand that the embodiments are only used to help understand the application and should not be regarded as specific limitations on the application.

[0057] Embodiment 1

[0058] The embodiment provides a method for recovering metals from waste ternary lithium battery positive electrode materials, and the method comprises the following steps:

[0059] (1) The waste ternary lithium battery positive electrode material is ground and sieved, and then dried at 105 DEG C for 2 hours to obtain a waste ternary lithium battery positive electrode material powder with a particle size D50 < 100.

[0060] The waste ternary lithium battery positive electrode material powder and a reducing agent are mixed and subjected to activation treatment to reduce transition metals in the waste ternary lithium battery positive electrode material powder; wherein the reducing agent is citric acid; and the temperature of the activation treatment is 200 DEG C.

[0061] (2) The waste ternary lithium battery positive electrode material powder after the activation treatment, polyvinylidene fluoride and conductive carbon black are dispersed in N,N-dimethylacetamide at a mass ratio of 85:10:5, uniformly stirred, and a mixed slurry with a solid content of 50wt% is prepared.

[0062] The mixed slurry is coated on a graphite sheet and dried to obtain an electrode sheet.

[0063] (3) The electrode sheet is used as an anode, a titanium electrode is used as a cathode, a lithium ion selective permeation membrane is used to separate the electrolytic cell into an anode chamber and a cathode chamber, and an oxidation-reduction reaction is carried out, so that nickel ions, cobalt ions and manganese ions are dissolved out in the electrolyte in the anode chamber, and lithium phosphate precipitates are formed in the cathode chamber.

[0064] The lithium ion selective permeation membrane is a lithium type molecular sieve, the lithium type molecular sieve is LTA type, the electrolyte of the anode chamber and the electrolyte of the cathode chamber are both ammonium phosphate solutions with a pH of 7.5; the parameters of the redox reaction include: an electrolysis voltage of 3V, a reaction temperature of 40℃, and a current density of 30mA / cm 2 .

[0065] (4) The electrolyte of the cathode chamber is filtered, and then the filtered lithium phosphate precipitate is subjected to acid dissolution, impurity removal, recrystallization, washing and drying to complete the purification treatment, thereby preparing a battery-grade lithium phosphate product.

[0066] The electrolyte of the anode chamber is subjected to post-treatment to obtain a nickel-cobalt-manganese mixed metal powder, and the specific steps include:

[0067] (a) A sulfuric acid solution is added to the electrolyte in the anode chamber, and acidification treatment is performed at a temperature of 60℃ to adjust the pH value of the electrolyte to 3.5, followed by the addition of hydrogen peroxide, and reaction is performed at a temperature of 40℃ to oxidize Mn 2+ to manganese oxide precipitate, and then filtration is performed to obtain a manganese-removed filtrate.

[0068] (b) The manganese-removed filtrate is subjected to co-extraction of nickel and cobalt ions, and then stripping is performed to transfer the nickel ions and cobalt ions to the aqueous phase, and after concentration and crystallization, a mixed salt of nickel sulfate and cobalt sulfate is obtained; wherein the extractant used in the co-extraction process is DY319, and the temperature in the co-extraction process is 50℃.

[0069] Example 2

[0070] The present embodiment provides a method for recovering metals from waste ternary lithium battery positive electrode materials, which comprises the following steps:

[0071] (1) The waste ternary lithium battery positive electrode material is ground and sieved, and then dried at 100℃ for 3h to obtain a waste ternary lithium battery positive electrode material powder with a particle size D50<100.

[0072] The waste ternary lithium battery positive electrode material powder and a reducing agent are mixed for activation treatment to reduce the transition metals in the waste ternary lithium battery positive electrode material powder; wherein the reducing agent is ascorbic acid; and the temperature of the activation treatment is 175℃.

[0073] (2) The waste ternary lithium battery positive electrode material powder after activation treatment, polyvinylidene fluoride and conductive carbon black are dispersed in N,N-dimethylacetamide at a mass ratio of 85:10:5, and stirred uniformly to prepare a mixed slurry with a solid content of 50wt%.

[0074] The mixed slurry is coated on a graphite sheet and dried to obtain an electrode sheet.

[0075] (3) Taking the electrode sheet as an anode and a titanium electrode as a cathode, the electrolytic cell is separated into an anode chamber and a cathode chamber by a lithium ion selective permeation membrane, and a redox reaction is carried out, so that nickel ions, cobalt ions and manganese ions are dissolved in the electrolyte in the anode chamber, and lithium phosphate precipitates are formed in the cathode chamber.

[0076] The lithium ion selective permeation membrane is a ceramic-polymer composite membrane, the ceramic-polymer composite membrane is a LATP and PVDF composite membrane, the electrolyte in the anode chamber and the electrolyte in the cathode chamber are both ammonium phosphate solutions with a pH of 6.5; the parameters of the redox reaction include an electrolysis voltage of 2V, a reaction temperature of 60℃, and a current density of 20mA / cm 2 .

[0077] (4) The electrolyte in the cathode chamber is filtered, and then the filtered lithium phosphate precipitate is subjected to acid dissolution, impurity removal, recrystallization, washing and drying to complete the purification treatment, thereby obtaining a battery-grade lithium phosphate product.

[0078] The electrolyte in the anode chamber is subjected to post-treatment to obtain a nickel-cobalt-manganese mixed metal powder, and the specific steps include:

[0079] (a) Adding a sulfuric acid solution to the electrolyte in the anode chamber and performing acidification treatment at a temperature of 50℃ to adjust the pH value of the electrolyte to 2, and then adding hydrogen peroxide and reacting at a temperature of 60℃ to oxidize Mn 2+ to manganese oxide precipitate, and then filtering to obtain a manganese-removed filtrate.

[0080] (b) Co-extracting nickel and cobalt ions from the manganese-removed filtrate, and then stripping to transfer the nickel ions and cobalt ions to the aqueous phase, and after concentration and crystallization, a mixed salt of nickel sulfate and cobalt sulfate is obtained; wherein the extractant used in the co-extraction process is DY319, and the temperature in the co-extraction process is 30℃.

[0081] Example 3

[0082] The present embodiment provides a method for recovering metals from waste ternary lithium battery positive electrode materials, which comprises the following steps:

[0083] (1) The waste ternary lithium battery positive electrode material is ground and sieved, and then dried at 110℃ for 1h to obtain a waste ternary lithium battery positive electrode material powder with a particle size D50<100.

[0084] The waste old ternary lithium battery positive electrode material powder and a reducing agent are mixed to perform activation treatment to reduce transition metals in the waste old ternary lithium battery positive electrode material powder; wherein the reducing agent is oxalic acid; the temperature of the activation treatment is 225 DEG C.

[0085] (2) The waste old ternary lithium battery positive electrode material powder after the activation treatment, polyvinylidene fluoride and conductive carbon black are dispersed in N, N-dimethylacetamide according to a mass ratio of 85:10:5, uniformly stirred to prepare a mixed slurry with a solid content of 50wt%.

[0086] The mixed slurry is coated on a graphite sheet, dried to obtain an electrode sheet.

[0087] (3) The electrode sheet is used as an anode, a titanium electrode is used as a cathode, a lithium ion selective permeation membrane is used to separate an electrolytic cell into an anode chamber and a cathode chamber, and a redox reaction is performed to dissolve nickel ions, cobalt ions and manganese ions in an electrolyte in the anode chamber and form lithium phosphate precipitates in the cathode chamber.

[0088] The lithium ion selective permeation membrane is a modified perfluorosulfonic acid resin membrane, the modified perfluorosulfonic acid resin membrane is a lithium type modification of a Nafion membrane, the electrolyte in the anode chamber and the electrolyte in the cathode chamber are both ammonium phosphate solutions with a pH of 8; the parameters of the redox reaction include an electrolytic voltage of 4V, a reaction temperature of 60 DEG C, and a current density of 50mA / cm 2 .

[0089] (4) The electrolyte in the cathode chamber is filtered, and then the filtered lithium phosphate precipitates are subjected to acid dissolution, impurity removal, recrystallization, washing and drying to complete purification treatment to prepare a battery-grade lithium phosphate product.

[0090] The electrolyte in the anode chamber is post-treated to obtain a nickel-cobalt-manganese mixed metal powder, and the specific steps include:

[0091] (a) Sulfuric acid solution is added to the electrolyte in the anode chamber and acidification treatment is performed at a temperature of 70 DEG C to adjust the pH value of the electrolyte to 5, and then hydrogen peroxide is added to react at a temperature of 30 DEG C to oxidize Mn 2+ to manganese oxide precipitates, and then the manganese-removed filtrate is obtained by filtration.

[0092] (b) The manganese-removed filtrate is subjected to co-extraction of nickel and cobalt ions, and then stripping to transfer the nickel ions and the cobalt ions to the aqueous phase, and after concentration and crystallization, a mixed salt of nickel sulfate and cobalt sulfate is obtained; wherein the extractant used in the co-extraction process is DY319, and the temperature in the co-extraction process is 80 DEG C.

[0093] Example 4

[0094] The difference between this embodiment and embodiment 1 is that no activation treatment is performed in step (1).

[0095] The remaining preparation methods and parameters remain consistent with embodiment 1.

[0096] Example 5

[0097] The difference between this embodiment and embodiment 1 is that the electrolyte in the anode chamber and the electrolyte in the cathode chamber in step (3) are both sodium hydroxide solutions with a concentration of 3 mol / L.

[0098] The remaining preparation methods and parameters remain consistent with embodiment 1.

[0099] Example 6

[0100] The difference between this embodiment and embodiment 1 is that no acidification treatment is performed in step (4).

[0101] The remaining preparation methods and parameters remain consistent with embodiment 1.

[0102] Comparative Example 1

[0103] The difference between this comparative example and embodiment 1 is that no electrode sheet is prepared, i.e., step (2) is not performed, and the waste ternary lithium battery positive electrode material powder is directly put into the electrolyte in the anode chamber.

[0104] The remaining preparation methods and parameters remain consistent with embodiment 1.

[0105] Comparative Example 2

[0106] The difference between this comparative example and embodiment 1 is that no lithium ion selective permeation membrane is provided in step (3).

[0107] The remaining preparation methods and parameters remain consistent with embodiment 1.

[0108] Performance Test

[0109] The products (lithium product, nickel-cobalt mixed metal powder) recovered by the methods provided in the above examples and comparative examples are tested for purity and recovery rate, and the purity test method is ICP-OES (inductively coupled plasma emission spectrometer) test method.

[0110] The test results are shown in Table 1.

[0111] Table 1

[0112]

[0113]

[0114] Analysis:

[0115] The present application synchronously solves the problems of low lithium purity, incomplete separation of transition metals and complex process in traditional recycling technology through precise separation mechanism and step-by-step regulation strategy, and provides an efficient, environmentally friendly and controllable process path for high-value recycling of valuable metals from waste ternary lithium batteries

[0116] It can be known from the comparison between Example 1 and Example 4 that if the step of activation is not performed in step (1), the transition metals in the waste ternary lithium battery positive material still exist in the crystal lattice in high valence state, are difficult to be dissolved by the subsequent electrolyte, and lead to the decrease of the transition metal dissolution rate; at the same time, the undamaged layered crystal lattice tightly binds Li+, which makes it difficult to separate from the crystal lattice and enter the electrolyte, and the lithium migration efficiency decreases, finally leading to the decrease of the separation purity of nickel and cobalt, the increase of the impurity content in the lithium product, and the decrease of the recovery rate of lithium metal and nickel-cobalt metal.

[0117] It can be known from the comparison between Example 1 and Example 5 that if the electrolyte in the anode chamber and the electrolyte in the cathode chamber are both sodium hydroxide solutions with a concentration of 3 mol / L, the strong alkaline environment will lead to the formation of hydroxide precipitates of Ni 2 , Co 2+ and Mn 2+ , and Li+ is easy to mix with the precipitates when migrating without complex protection, which leads to the decrease of lithium purity, and the strong alkali will corrode the lithium ion selective permeation membrane, which shortens the service life of the membrane.

[0118] It can be known from the comparison between Example 1 and Example 6 that if the acidification treatment is not performed in step (4), the electrolyte in the anode chamber still maintains weak alkalinity, and Mn 2+ exists in the form of a complex, and the oxidizing agent is difficult to oxidize it into manganese oxide precipitate, which leads to the excessive content of manganese impurities in the final nickel-cobalt mixed metal and the decrease of the purity.

[0119] It can be known from the comparison between Example 1 and Comparative Example 1 that if the waste ternary lithium battery positive material powder is directly put into the electrolyte in the anode chamber, the powder is easy to be dispersed unevenly due to the lack of current collector support and the conduction of conductive agent, the contact area between the powder and the electrolyte is unstable, the electron transfer is blocked, the anode reaction efficiency decreases, and the transition metal dissolution rate decreases; at the same time, the suspended powder increases the viscosity of the electrolyte, hinders the migration of Li+, and the un-fixed powder is easy to flow with the electrolyte and block the lithium ion selective permeation membrane, which leads to the decrease of the membrane flux and the shortening of the service life of the membrane. In addition, the inert impurities in the powder will mix into the product during the reaction, which leads to the decrease of the purity of the nickel-cobalt mixed metal and the increase of the impurity content of the lithium product.

[0120] It can be known from the comparison between Example 1 and Comparative Example 2 that if the lithium ion selective permeation membrane is not set, the transition metal ions in the anode chamber will freely diffuse to the cathode chamber, which pollutes the lithium product, leads to the decrease of the purity, and the separation of lithium and nickel-cobalt is not complete, at the same time, the purity of the nickel-cobalt co-precipitate decreases, the recovery rate decreases, and the process stability is poor.

[0121] It should be noted that the process of the present application is illustrated by the above examples, but the present application is not limited to the above examples, i.e. it does not mean that the present application must rely on the above examples to be implemented. It should be understood by those skilled in the art that any improvement of the present application, equivalent replacement of each raw material of the product of the present application, addition of auxiliary ingredients, selection of specific modes, etc. fall within the protection scope and disclosure scope of the present application.

Claims

1. A method for recovering metals from the cathode material of spent ternary lithium batteries, characterized in that, The method includes the following steps: A mixed slurry is prepared by mixing waste ternary lithium battery cathode material, binder, conductive agent and organic solvent; the mixed slurry is then coated onto a current collector to obtain an electrode sheet. Using the electrode sheet as the anode and the inert electrode as the cathode, the electrolytic cell is divided into an anode chamber and a cathode chamber by a lithium-ion selective permeation membrane to carry out redox reactions, thereby dissolving transition metal ions in the electrolyte in the anode chamber and forming lithium phosphate precipitate in the cathode chamber. The electrolyte in the anode chamber is post-treated to obtain a nickel-cobalt mixed metal salt.

2. The method according to claim 1, characterized in that, Before mixing the waste ternary lithium battery cathode material, binder, conductive agent and organic solvent, the waste ternary lithium battery cathode material is first activated to reduce the transition metals in the waste ternary lithium battery cathode material. Preferably, the reducing agent used in the activation process includes any one or a combination of at least two of citric acid, ascorbic acid, or oxalic acid; Preferably, the activation treatment temperature is 150-300℃.

3. The method according to claim 1 or 2, characterized in that, The adhesive includes any one or a combination of at least two of polyvinylidene fluoride, styrene-butadiene rubber, or carboxymethyl cellulose. Preferably, the conductive agent includes any one or a combination of at least two of conductive carbon black, carbon nanotubes, or graphene; Preferably, the solid content of the mixed slurry is 30-70 wt%. Preferably, the current collector comprises a graphite sheet; Preferably, the inert electrode includes any one of a graphite electrode, a titanium electrode, or a platinum electrode.

4. The method according to any one of claims 1-3, characterized in that, The lithium-ion selective permeation membrane is any one of lithium molecular sieve, ceramic-polymer composite membrane, ceramic membrane, or modified perfluorosulfonic acid resin membrane.

5. The method according to any one of claims 1-4, characterized in that, The electrolyte in both the anode chamber and the cathode chamber is an ammonium phosphate solution.

6. The method according to any one of claims 1-5, characterized in that, The pH of the electrolyte in the anode chamber and the electrolyte in the cathode chamber is 6.5-8.

7. The method according to any one of claims 1-6, characterized in that, The parameters of the redox reaction include: The electrolysis voltage is 2-4V, the reaction temperature is 25-60℃, and the current density is 10-200mA / cm². 2 .

8. The method according to any one of claims 1-7, characterized in that, The post-processing includes the following steps: The electrolyte in the anode chamber is acidified, and then an oxidant is added to make Mn 2+ Oxidation produces manganese oxide precipitate; filtration is performed, and then the filtrate is co-extracted for nickel and cobalt ions to obtain a mixed salt of nickel and cobalt salts.

9. The method according to claim 8, characterized in that, The acid solution added during the acidification process includes sulfuric acid; Preferably, the pH value of the acidified electrolyte is 2-5; Preferably, the acidification treatment temperature is 50-70°C; Preferably, the extractant used in the co-extraction process includes DY319 and / or HBL110; Preferably, the temperature during the co-extraction process is 30-80℃.

10. The method according to any one of claims 1-9, characterized in that, The method includes the following steps: (1) Grind and sieve the waste ternary lithium battery cathode material, and then dry it at 100-110℃ for 1-3 hours to obtain waste ternary lithium battery cathode material powder with particle size D50 < 100 mesh. The waste ternary lithium battery cathode material powder is mixed with a reducing agent to reduce the transition metals in the waste ternary lithium battery cathode material powder; wherein, the reducing agent includes any one or a combination of at least two of citric acid, ascorbic acid or oxalic acid; the activation treatment temperature is 150-300℃; (2) The activated waste ternary lithium battery cathode material powder, binder, conductive agent and organic solvent are mixed to prepare a mixed slurry with a solid content of 30-70 wt%; wherein, the binder includes any one or a combination of at least two of polyvinylidene fluoride, styrene-butadiene rubber or carboxymethyl cellulose, and the conductive agent includes any one or a combination of at least two of conductive carbon black, carbon nanotubes or graphene; The mixed slurry is coated onto a graphite sheet and dried to obtain an electrode sheet; (3) Using the electrode sheet as the anode and the inert electrode as the cathode, the electrolytic cell is divided into an anode chamber and a cathode chamber by a lithium ion selective permeation membrane to carry out redox reactions, thereby dissolving nickel ions, cobalt ions and manganese ions in the electrolyte in the anode chamber and forming lithium phosphate precipitate in the cathode chamber. The lithium-ion selective permeation membrane is any one of lithium-type molecular sieve, ceramic-polymer composite membrane, ceramic membrane, or modified perfluorosulfonic acid resin membrane; the inert electrode includes any one of graphite electrode, titanium electrode, or platinum electrode; the electrolyte in both the anode and cathode chambers is an ammonium phosphate solution with a pH of 6.5-8; the parameters of the redox reaction include: an electrolysis voltage of 2-4V, a reaction temperature of 25-60℃, and a current density of 10-200mA / cm³. 2 ; (4) The electrolyte in the cathode chamber is filtered and then purified to obtain battery-grade lithium phosphate product. The electrolyte in the anode chamber is post-treated to obtain a nickel-cobalt-manganese mixed metal powder. The specific steps include: (a) Add acid to the electrolyte in the anode chamber and acidify it at 50-70°C to adjust the pH of the electrolyte to 2-5. Then add an oxidant and react at 20-60°C to allow Mn to react. 2+ The solution is oxidized to manganese oxide precipitate, then filtered to obtain a demanganese-removed filtrate; the oxidizing agent includes hydrogen peroxide. (b) The demanganese filtrate is co-extracted with nickel and cobalt ions, and then back-extracted to transfer nickel and cobalt ions into the aqueous phase. After concentration and crystallization, a mixed salt of nickel and cobalt salts is obtained. The extractant used in the co-extraction process includes DY319 and / or HBL110, and the temperature during the co-extraction process is 30-80°C.